An Error Analysis on the Teacher-Made Materials: Exploring a Possible Use of Technical Rhetoric - Philipus Pirenimulyo (Dinamika Bahasa dan Budaya, 2008)
There is in the English for Specific Purposes (ESP) a lack of pedagogically appropriate materials for the teaching of reading skills in the field of science and technology, in spite of the abundant number of publications in the English language which should be read by our students in order for the newly developed knowledge to be transferred and or for further studies and application. For teachers of ESP, this phenomenon gives a great challenge to provide a good variety of topics in the area for teaching-learningpurposes. In this paper an attempt is made to make use of the rhetoric aspects of a technological text available. In summary, the conceptual and physical paragraph structure of a text may be utilized for the construction of own-made appropriate and sound teaching materials to meet the need of the students. Key word: EST, rhetoric principles, learner needs, conceptual paragraph, physical paragraph